Tawakal kepada Allah Memprediksi Resiliensi Akademik pada Pembelajaran Online - Aryan Muhaimin Saputra; Abdullah Faruqi; Irwan Nuryana Kurniawan (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to examine the role of tawakal (trust) to Allah on academic resilience. This study used quantitative correlational method. The participants were 202 individuals consisted of high school and university students recruited through voluntary sampling. The regression analysis results show that tawakal to Allah predicts academic resilience significantly with high effective contribution. Besides, two aspects of tawakal to Allah predict academic resilience significantly are belief to Allah and worship aspects. Tawakal to Allah can be a religious coping to help students overcome the difficulties of online learning. Future research can consider tawakal to Allah as an effective predictor and intervention for academic resilience.